Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/conphys/coz068
|View full text |Cite
|
Sign up to set email alerts
|

Only as strong as the weakest link: structural analysis of the combined effects of elevated temperature and pCO2 on mussel attachment

Abstract: Predicting how combinations of stressors will affect failure risk is a key challenge for the field of ecomechanics and, more generally, ecophysiology. Environmental conditions often influence the manufacture and durability of biomaterials, inducing structural failure that potentially compromises organismal reproduction, growth, and survival. Species known for tight linkages between structural integrity and survival include bivalve mussels, which produce numerous byssal threads to attach to hard substrate. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The energetic trade‐off between thread production and tissue growth can be characterized with a SFG model (Figure 1). Mussels modulate their production of byssal threads in response to a range of environmental conditions, such as increased wave disturbance (Bell & Gosline, 1997; Carrington et al., 2008; Dolmer & Svane, 1994; Lee et al., 1990; Moeser et al., 2006; Van Winkle, 1970; Young, 1985), seawater temperature and pH (George et al., 2018; Newcomb et al., 2019; O’Donnell et al., 2013), as well as seasonal and/or reproductive cycles in natural systems (Carrington, 2002; Moeser & Carrington, 2006; Newcomb, 2015; Zardi et al., 2007). Within the framework of a SFG model, the theoretical variable, SFG, can be used an index of tissue growth (including gonadal and somatic tissue growth), and is calculated as the difference between consumption minus physiological cost (Bayne et al., 1976; Sebens, 2002; Widdows & Bayne, 1971; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The energetic trade‐off between thread production and tissue growth can be characterized with a SFG model (Figure 1). Mussels modulate their production of byssal threads in response to a range of environmental conditions, such as increased wave disturbance (Bell & Gosline, 1997; Carrington et al., 2008; Dolmer & Svane, 1994; Lee et al., 1990; Moeser et al., 2006; Van Winkle, 1970; Young, 1985), seawater temperature and pH (George et al., 2018; Newcomb et al., 2019; O’Donnell et al., 2013), as well as seasonal and/or reproductive cycles in natural systems (Carrington, 2002; Moeser & Carrington, 2006; Newcomb, 2015; Zardi et al., 2007). Within the framework of a SFG model, the theoretical variable, SFG, can be used an index of tissue growth (including gonadal and somatic tissue growth), and is calculated as the difference between consumption minus physiological cost (Bayne et al., 1976; Sebens, 2002; Widdows & Bayne, 1971; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, in shallow coastal waters with limited water exchange rates high water temperatures can appear during summer. Fly and Hilbish (2013) stated that the energetic balance of M. trossulus is affected by water temperatures above 17 • C. Other studies have shown that byssus threads are up to 60% weaker at water temperatures of 25 • C than at 10 • C (Newcomb et al, 2019). Westerbom et al (2019) concluded that temperature stress coupled with continuous salinity stress may also cause increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Fly and Hilbish (2013) stated that the energetic balance of M. trossulus is affected by water temperatures above 17 °C. Other studies have shown that byssus threads are up to 60% weaker at water temperatures of 25 °C than at 10 °C ( Newcomb et al, 2019 ). Westerbom et al.…”
Section: Introductionmentioning
confidence: 97%
“…Larval growth, calcification rates and overall health of M. edulis will be inhibited during this same time period (Gazeau et al 2007;Beesley et al 2008;Gazeau et al 2010), but several studies (Beesley et al 2008;Thomsen & Melzner, 2010;Dickey et al 2018) suggest that M. edulis metabolism, tissue condition and thread production will not be affected. In contrast, studies with Mytilus trossulus (Gould 1850) on the U.S. Washington coast found that byssal thread number and attachment strength were negatively affected by higher temperature (25°C versus 10°C) and secreted adhesives did not cure well at pH < 8 (O'Donnell et al 2013; George & Carrington 2018;Newcomb et al 2019). Mytilus trossulus also occurs in Maine (especially in Bioregion 3), suggesting the usefulness of additional studies of adhesive plaques and thread strength in Maine for both M. edulis and M. trossulus, because failure of these structures due to climate change could have significant negative implications for mussel aquaculture.…”
Section: Acidification Impactsmentioning
confidence: 99%
“…2013; George & Carrington 2018; Newcomb et al . 2019). Mytilus trossulus also occurs in Maine (especially in Bioregion 3), suggesting the usefulness of additional studies of adhesive plaques and thread strength in Maine for both M. edulis and M. trossulus , because failure of these structures due to climate change could have significant negative implications for mussel aquaculture.…”
Section: Resilience Of the Aquaculture Industrymentioning
confidence: 99%